Warehouse location selection in retail industry using machine learning and multi criteria decision making - Kazaz, Nadi (My University, 2022)
Artan rekabet koşullarında firmaların faaliyetlerini devam edebilmeleri için doğru kararlar almaları gerekmektedir. Bu çalışmada bir perakende firması Türkiye’nin her bölgesine birer adet depo açmayı amaçlamaktadır. En uygun depo yeri seçiminde en az 2 seçenek ve en az 2 kriter bulunmaktadır. Bu durumda şirket en uygun alternatifleri seçebilmek için kanıtlanmış modellere sahip olmalıdır. Bu çalışmanın amacı, en az 2 alternatif ve en az 2 kriterin olduğu durumlarda en uygun alternatiflerin nasıl belirleneceğini göstermektir. En az 2 alternatif ve en az 2 kriterin olduğu durumlarda çok kriterli karar verme tekniklerinden biri kullanılabilir. Bu çalışmada kriterlerin ağırlıklarının belirlenmesinde Saaty Metodu, Entropi Metodu ve Gini Metodu kullanılmıştır. Bu veriler doğrultusunda ayrı ayrı TOPSIS metodu uygulanmıştır. TOPSIS metodunun işlem adımları da Excel üzerinde formüle edilmiştir. Ayrıca çalışmada makine öğrenmesinde denetimsiz öğrenmenin bir kolu olan k-means algoritması da kullanılmıştır. K-means algoritması ile bölgesel bazlı olmayan ve bölgesel bazlı olan 2 farklı kümeleme çalışması gerçekleştirilmiştir. Gini Metodu için, Rastgele Orman Teoremi kullanılmıştır. Bu sayede, 5 farklı yöntem ile en uygun depo yeri seçimi karşılaştırılmıştır.

In the circumstances of soaring rivalry, corporations must perform the right decisions in order to maintain their actions. In this implementation, a retail corporation intends so as to open a warehouse in each region of Turkey. There are at least two alternatives and at least two criteria in selecting the most convenient warehouse location. At that rate, the corporations must have a proven models to be able to select the best convenient alternatives. The aims of this implementation is to demonstrate how to find the most convenient alternatives in situations where there are at least two alternative and at least two criteria. In situations where there are at least two alternatives and at least two criteria, one of the Multi Criteria Decision Making techniques may be utilized. For the implementation, Saaty Method, Entropy Method and Gini Method were utilized to determine the weights of the criteria. In line with these data, the Topsis Method was applied separately. The operation steps of the TOPSIS method are formulated on Excel. In addition, the k-means algorithm, which is a branch of unsupervised learning in machine learning, was also used in the study. With the k-means algorithm, 2 different clustering studies, which are not regional based and regional based were carried out. The Random Forest Method is utilized for the Gini Method. In this way, the most suitable warehouse location selection was compared with 5 different methods.
Keywords: Çok Kriterli Karar Verme; Depo Multi Criteria Decision Making; Endüstri mühendisliği; Industrial engineering; Machine Learning; Makine Öğrenimi; Topsis; Warehouse